The Effectiveness of an Educational Program According to the Analytical Thinking Method in Developing Academic Motivation among Undergraduate Students in the Curricula and Teaching Methods Course - Hassain Abdal Hady, Shaimaa; Sahib Mussa AL. Zuwainy, Ibtisam (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to know the effectiveness of an educational program according to the analytical thinking method in developing academic motivation among university students in the curriculum and general teaching methods. To verify the research goal, the two researchers imposed the following null hypothesis: Students of the experimental group who will study according to the educational program and the average scores of the control group students who will study according to the usual way in the achievement test. To achieve this, the two researchers chose an experimental design with partial control, as they intentionally chose the College of Education at the basic Babylon University to conduct the experiment. The research sample consisted of sixty (60) male and female students: thirty (30) male and female students of the experimental group and thirty (30) male and female students of the control group. The researcher studied the experimental group in the educational program and studied the control group in the usual way. Psychometric testing of the test and the application of the experiment continued for 8 weeks, and at the end of the experiment, the achievement test was applied to the two groups. After that, the results were analyzed and showed the superiority of the experimental group students who studied according to an educational program over the control group who studied the usual way.